Development of an Ecotheology-Based Islamic Education Learning Model from the Perspective of Classical and Contemporary Islamic Education - Alfani; Eko Sugianto; Solikin; Salim (Civiliza Publishing, Indonesia., 2026)
This study aims to develop an ecotheology-based Islamic Religious Education (PAI) learning model from the perspective of classical and contemporary Islamic education as an effort to build students' ecological awareness amidst the global environmental crisis. This research is motivated by the fact that PAI learning tends to be normative and textual, thus failing to integrate ecological values ​​contextually into students' lives. The study uses a Research and Development (R&D) approach with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The results show that the ecotheology-based PAI learning model has a strong philosophical foundation in classical Islamic education through the concepts of adab, morals, and human responsibility as khalifah fil ardh, and is strengthened by a contemporary Islamic education approach that is integrative, contextual, participatory, spiritual-ecological, and oriented towards building students' character. The implementation of the model is carried out through curriculum integration, the use of active learning methods, the habituation of a green school culture, teacher role models, and collaboration with the community. Thus, the development of an ecotheology-based Islamic Education learning model is expected to be able to form students who not only have spiritual piety, but also ecological awareness and social responsibility towards environmental sustainability.